ANALISIS FAKTOR KETERLAMBATAN BERBICARA (SPEECH DELAY) ANAK USIA 6 TAHUN - Yuliatul Rohimah; Raden Rachmy Diana (JS (JURNAL SEKOLAH), 2022)
Abstract : Speech delay greatly affects the language development of early childhood. Because language is a connecting tool in communicating when interacting in a social environment. This study was conducted with the aim of analyzing the effect of speech delay suffered by children aged 6 years. The type of research used is descriptive qualitative research with a case study approach. This research uses SSR (Single Subject Research) technique. Data obtained through observation, interviews, and documentation. Based on the results of the analysis of speech delay factors in children, it was found that 1) male gender 2) genetics, or heredity 3) lack of stimulus from parents, 4) at the age of 1 year his head hit a hard object until it became swollen, 5) lack of developmental support in communicating with the environment. As a result, the delay in speaking that children experience causes obstacles to the development of language, social, motor, and intelligence levels of children.Keywords: Speech Delay, Language Development, Children aged 6 yearsAbstrak : Keterlambatan berbicara (speech delay) sangat memperngaruhi bagi perkembangan bahasa anak usia dini. Karena bahasa sebagai alat penyambung dalam berkomunikasi ketika berinteraksi dilingkungan sosial. Penelitian ini dilakukan dengan tujuan menganalisis pengaruh keterlambatan berbicara (speech delay) yang diderita anak berumur 6 tahun. Penelitian yang digunakan yakni jenis penelitian deskriptif kualitatif dengan pendekatan studi kasus. Penelitian ini menggunakan Teknik SSR (Single Subject Research). Data diperoleh melalui observasi, wawancara, dan dokumentasi. Berdasarkan hasil analisis faktor keterlambatan berbicara pada anak yang ditemukan yaitu 1) Jenis kelamin laki-laki 2) genetik, atau keturunan 3) kurangnya stimulus dari orang tua, 4) pada usia 1 tahun kepalanya terantuk benda keras sampai bengkak, 5) tidak cukup dukungan perkembangan dalam berkomunikasi dilingkungan sekitar. Akibatnya keterlambatan berbicara yang anak alami menyebabkan hambatan pada perkembangan bahasa, sosial, motorik, dan tingkat kecerdasan anak.Kata Kunci : Keterlambatan Berbicara, Perkembangan Bahasa, Anak Usia 6 tahun